The maximum tensor complementarity eigenvalues. (1st November 2020) - Fan, Jinyan; Nie, Jiawang; Zhao, Ruixue
ABSTRACT: This paper proposes an algorithm for computing the maximum (or minimum) complementarity eigenvalues of tensors. We formulate this as proper polynomial optimization problems that can be efficiently solved by Lasserre type semidefinite relaxations. The algorithm is proved to have finite convergence for generic tensors.